Brief evaluation of pleasantness of olfactory and trigeminal stimulants - Vodicka, Jan; Meloun, Milan; Príhodová, Lucie (Archives of otolaryngology--head & neck surgery, 2010)
OBJECTIVE: To evaluate a brief olfactory test based on pleasantness rating of olfactory and trigeminal stimulants. DESIGN: Criterion standard. SETTING: University hospital. PARTICIPANTS: A total of 60 participants (48 healthy and 12 with olfactory loss) aged 16 to 81 years. INTERVENTIONS: The new test of odor pleasantness (TOP) based on classification of odorants and trigeminal stimulants into 4 categories was compared with 2 standard tests of subjective olfactometry. MAIN OUTCOME MEASURE: We evaluated the possible use of the TOP in assessment of olfactory and the trigeminal system in healthy individuals and those with olfactory loss. RESULTS: All 3 tests demonstrated significant mutual correlation (P < .01), and persons with olfactory loss scored lower than healthy participants (P < .01). Using exploratory factor analysis and cluster analysis, we found that healthy individuals classified odorants accurately according to the degree of their hedonic character. CONCLUSION: The TOP offers outcomes similar to those of standard tests of olfaction that are based on psychophysical testing.
Keywords: Young Adult; Olfaction Disorders; poruchy čichu; Male; mladý dospělý; Odorants; nervus trigeminus; Adolescent; Adult; Trigeminal Nerve; Aged; dospělí; mužské pohlaví; senioři; odoranty; mladiství; senioři nad 80 let; lidé; ženské pohlaví; Humans; Aged, 80 and over; Female; Olfactory Perception; lidé středního věku; čichová percepce; Middle Aged